Preparation, electrochemistry and optical properties of unsymmetrical phthalocyanines bearing morpholine and tert-butylphenoxy substituents - KOCA, ATIF (ELSEVIER SCIENCE SA, 2011)
The synthesis of novel, unsymmetrical, octasubstituted metal-free and metallophthalocyanines (zinc, cobalt) bearing one chlorine, one morpholine moieties and six 4-tert-butylphenoxy substituents was achieved by a statistical condensation reaction of two corresponding phthalonitriles. The new compounds have been characterized by using elemental analyses, UV-vis, IR, (1)H NMR and mass spectroscopic data. Voltammetric and spectroelectrochemical studies are in harmony with the reported metallophthalocyanine complexes, which support the proposed structure of the complexes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; Phthalocyanine; Spectroelectrochemistry; Unsymmetric; Zinc; MOLECULAR-ORBITAL CALCULATIONS; POLYMER SUPPORT; METALLOPHTHALOCYANINES; SUBPHTHALOCYANINES; DERIVATIVES; COMPLEXES; SUBNAPHTHALOCYANINES; SUBAZAPORPHYRINS; NANOPARTICLES; SPECTROSCOPY